(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
Humor and satire occupy a central place in the literary heritage of Mark Twain, one of the most prominent figures in American literature. Twain’s short stories demonstrate a unique combination of wit, irony, and social criticism, allowing him to depict the realities of nineteenth-century American society with remarkable vividness. This article examines the artistic role of humor and satire in Mark Twain’s short stories and analyzes the narrative techniques through which these devices function. Particular attention is given to Twain’s use of exaggeration, irony, colloquial language, and comic situations to reveal social contradictions and human weaknesses. The study demonstrates that humor and satire in Twain’s works are not merely sources of entertainment but powerful artistic tools that contribute to social critique and deepen the thematic significance of his stories.